Geomorphology of Topocalma’s active dune field, Central Chile: Contributions of the photogrammetric method through the use of UAV - Zúñiga Romero, Javiera; Cabrera, Felipe Thomas; L,eyton, Sebastián Sobarzo (Revista Brasileira de Geomorfologia, 2026)
The objective of this article was to carry out a geomorphological study of Topocalma’s dune field through a photogrammetric survey using a drone, a methodology that has not been used to study dune fields in Chile. As a system with little intervention, the selection of the area particularly lies in the lack of further dune field geomorphological investigation. However, adjacent areas present relevant anthropogenic pressures; therefore, the use of new methodologies could contribute to its conservation and preventive planning. A dense point cloud, a digital elevation model and, an orthomosaic were obtained from an aerial photogrammetric survey carried out with a UAV. Subsequently, a morphometric characterization is carried out based on the height, slope and orientation of shapes, to generate a 3D model and a geomorphological map. The beach morphology and the formation of protodunes (bedform) of these last products were identified, when receiving a greater supply of sand form barchans, barchanoids and transverse dunes. Hence, a transgressive dune field was configured, which evolved towards an aklé pattern and parabolic dunes, at the same time.